Distinct signatures of gut microbiome and metabolites associated with significant fibrosis in non-obese NAFLD - Giljae Lee (Nature Portfolio, 2020)
Nonalcoholic fatty liver disease (NAFLD) is associated with obesity but also found in individuals without obesity. Here, gut microbiome analysis using a biopsy-proven NAFLD cohort reveal distinct signatures of microbiome-metabolites associated with significant fibrosis in patients with NAFLD without obesity.